Norman Fairclough's Thoughts on Linguistic Capitalism: The Technologization of Discourse and Language Management in Economy - Munthe, Yesyurun; Putri , Kesia Rosalina; Sinta, Grasela; Sihombing, Octa Maria; Carolina, Venesa (Indonesian Scientific Publication, 2023)
The aim of this research is to re-examine Norman Fairclough's concepts of discourse, critical discourse on media, language, technology, and management. Despite capitalism historically bringing ideals in the name of economic improvement after the Second World War, in practice, the commodification of language and economy became inevitable. Therefore, it is crucial to incorporate Norman Fairclough's notion of critical awareness of political agendas within the language spectrum in the analysis. The language used is clear, concise, and objective, with a logical flow of information and causal connections between statements. This text presents a qualitative research method that involves collecting data from primary and secondary sources. The results demonstrate that Norman Fairclough's concept of language in the context of management, discourse, technology, music, and policy serves as a platform for discourse development and as a tool to resist the commodification of meaning and ideology in a multifaceted landscape. Furthermore, Fairclough's ideas have contributed to the critical development of discourse analysis, which not only applies to specific disciplines but also to conversations in the humanities.